The Relationship between Financial Resilience Disclosure and Stock Returns from Investors’ Perspectives: An Exploratory Study in the Iraqi Stock Exchange - abed Khachi Hamad , Jinan; Diwan Shniwer Al-Jaberi , Mohammed; Mohammed Shanan , Ali (Iraqi Journal for Administrative Sciences, 2026)
This research aims to demonstrate the extent to which stakeholders (traders) are aware of the role of disclosing financial soundness indicators in enhancing the transparency of accounting and financial information, and the impact of this on stock returns. This awareness enables them to make sound financial decisions. The study employed a descriptive-analytical approach, relying on a field questionnaire administered to a random sample of investors and traders in the Iraq Stock Exchange. The data were statistically analyzed using a simple linear regression model. The analysis results showed that the regression coefficient value was (0.839), which translates the level of awareness among traders of a direct relationship between the level of disclosure of financial soundness indicators and stock returns. That is, traders believe that any increase in disclosure by one unit is associated with an increase in stock returns by (0.839). The (T) test, which reached (16.610) with a significance level (Sig=0.00) less than (0.05), confirmed the statistical significance of this relationship. The research concluded that the disclosure of financial soundness indicators is a fundamental pillar in enhancing traders' confidence and supporting the strength of their investment decisions, in addition to being a key entry point for the stability of the Iraqi financial market and improving governance and risk management practices.